PENGARUH EKSPEKTASI DAN KOMPLEKSITAS INFORMASI TERHADAP IKLAN PADA KETERLIBATAN, SIKAP TERHADAP IKLAN DAN MEREK DENGAN NEED FOR COGNITION SEBAGAI PEMODERASI - Terry Castello (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2009)
This study focused on consumer attitudes towards advertising. Many factors influenced consumer attitudes toward advertisement. This study explored the influence of two factors: consumer visual expectation and complexity of message delivery. 120 respondents have been involved and ANOVA has been employed in the study. Findings showed that advertising using unexpected visual information has more influence on advertising message involvement and consumer attitude toward advertisement than advertising using expected visual information. The findings also indicated that the need of cognition is a moderating variable for expected visual consumers and complexity of advertising message on consumer attitudes toward adverting. Keyword: need for cognition, consumer attitude, advertising, unexpected visual information,expected visual information